Method for analyzing relation between solid solution continuous cooling speed of high-temperature alloy and structure morphology and / or mechanical property and application
By coating the surface of high-temperature alloy specimens with insulation materials of different thicknesses and regulating the cooling rate, the problems of large cooling rate gradients and inaccurate cooling rates in the existing technology are solved, and the process control window of high-temperature alloys is determined.
Patent Information
- Application Number
- CN202411637671.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to accurately regulate the solid solution continuous cooling rate of high-temperature alloys, resulting in a large cooling rate gradient, making it difficult to collect the mechanical properties corresponding to different cooling rates, and the cooling rate is usually constant cooling, which is different from the actual working conditions.
By coating the surface of the high-temperature alloy sample with insulation materials of different thicknesses, the heat exchange boundary conditions are changed, the cooling speed is accurately controlled, and a cooling curve that is first fast and then slow near actual working conditions is achieved.
It achieves precise control of the cooling rate, close to actual working conditions, collects the microstructure and mechanical properties of the alloy corresponding to different cooling rates, and establishes the correlation between the cooling rate and the structural morphology and mechanical properties, thereby determining the process control window for the heat treatment of high-temperature alloys .
Smart Images

Figure CN119335001A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat treatment of high temperature alloys, and in particular to a method and application for analyzing the relationship between solid solution continuous cooling rate and microstructure and / or mechanical properties of high temperature alloys. Background Art
[0002] High-temperature alloys are widely used in aerospace and other fields due to their excellent mechanical properties. Among them, the γ′ phase is the main strengthening phase in high-temperature alloys. Its size, distribution morphology, and volume fraction are important factors affecting its strengthening effect, and the cooling rate after solid solution is the determining factor affecting the γ′ phase, which in turn affects the mechanical properties of the alloy at high temperatures. Therefore, it is necessary to establish a test method for the mechanical properties of high-temperature alloys after solid solution continuous cooling, collect the mechanical properties of the main high-temperature alloys after continuous cooling, and form a process control window for the heat treatment of the alloy.
[0003] Different parts of high-temperature alloy bars, disks, and rings have different cooling rates during the continuous cooling process, usually ranging from 20 to 200 °C / min. Figure 1 In the continuous cooling process, the cooling rate in the high temperature range of 700-1000°C is fast, and the cooling rate in the low temperature range of 300-700°C is slow.
[0004] In the prior art, cylindrical test bars are used to treat samples by water quenching, oil quenching, and air cooling after solution heat treatment. The size of the cylindrical test bar is determined according to the subsequent high-temperature tensile test, usually φ12×76mm. The advantage of this method is that it is easy to operate; the disadvantage is that the cooling rate of the small cylindrical test bar in the high-temperature section is too fast during water quenching, oil quenching, and air cooling. The average cooling rate in the high-temperature section of the cylindrical test bar during water quenching exceeds 2000℃ / min, and air cooling will also exceed 400℃ / min, which is much faster than the cooling rate inside the high-temperature alloy disc and ring.
[0005] In the prior art, the sample is end-quenched, a cylindrical sample (usually with a size of φ30×150 mm, or larger) is cut, and one end of the cylindrical sample is cooled, while the remaining end surface and the circumferential wall surface are prevented from cooling, thereby creating a gradient average cooling rate in a sample (e.g. Figure 2 The microstructures at different locations are then observed to establish the relationship between the average cooling rate and the microstructure. The disadvantage of this method is that the cooling rate gradient is large, and it is difficult to collect the mechanical properties corresponding to different cooling rates.
[0006] The existing technology uses thermal expansion instruments and thermomechanical coupling test machines (such as MTS, GLEEBLE, etc.) to perform thermal simulation on round bar samples. The advantages of this method are: easy to operate, and the cooling rate of the sample can be controlled. Disadvantages: The cooling rate is usually constant, which is different from the actual cooling curve where high temperature is fast and low temperature is slow, such as Figure 3shown.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The purpose of the present invention is to provide a method and application for analyzing the relationship between the continuous cooling rate of solid solution and the microstructure and / or mechanical properties of high-temperature alloys. The method for analyzing the relationship between the continuous cooling rate of solid solution and the microstructure and / or mechanical properties of high-temperature alloys can accurately control the cooling rate to achieve a cooling curve that is fast first and then slow, which is close to the actual working condition. It can approach the post-solid solution cooling rate corresponding to different areas of a disk or annular part, establish the correlation between the cooling rate and the microstructure and / or mechanical properties, and thus determine the process control window for heat treatment of high-temperature alloys.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] One aspect of the present invention relates to a method for analyzing the relationship between the solid solution continuous cooling rate and the microstructure and / or mechanical properties of a high-temperature alloy, comprising the following steps:
[0011] (a) The surface of the high-temperature alloy sample was coated with insulation materials of different thicknesses and then subjected to solution heat treatment, cooling and aging heat treatment;
[0012] (b) performing microstructural observation and / or mechanical property testing on the sample after the aging heat treatment to establish a correlation between the cooling rate and the microstructure and / or mechanical property.
[0013] The method for analyzing the relationship between the continuous solution cooling rate and the microstructure and / or mechanical properties of the high-temperature alloy can accurately control the cooling rate and realize a cooling curve that is fast first and then slow, which is close to the actual working condition. It can approach the post-solid solution cooling rate corresponding to different areas of the disk / ring, establish the relationship between the cooling rate and the microstructure and / or mechanical properties, and thus determine the process control window for heat treatment of the high-temperature alloy.
[0014] Another aspect of the present invention also relates to a method for optimizing the heat treatment process of a high-temperature alloy, including the method for analyzing the relationship between the solid solution continuous cooling rate and the microstructure and mechanical properties of the high-temperature alloy.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The method provided by the present invention for analyzing the relationship between the solid solution continuous cooling rate and the microstructure and / or mechanical properties of a high-temperature alloy comprises coating the surface of a high-temperature alloy sample with heat-insulating materials of different thicknesses, thereby changing the heat exchange boundary conditions, being able to accurately control the cooling rate, and realizing a cooling curve that is fast first and then slow, close to the actual working condition, and being able to approach the post-solid solution cooling rate corresponding to different areas of a disk / ring; collecting the alloy micromorphology, structure and mechanical properties corresponding to different cooling rates, establishing a correlation between the cooling rate and the structure morphology and / or mechanical properties, and thereby determining the process control window for heat treatment of the high-temperature alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 is the cooling rate of different parts of the high-temperature alloy during the continuous cooling process;
[0019] Figure 2 is the cooling rate of the end-quenched sample in the continuous cooling process;
[0020] Figure 3 is the cooling rate in the continuous cooling process of the thermal simulation method;
[0021] Figure 4 It is a schematic diagram of coating the surface of a high-temperature alloy with a thermal insulation material;
[0022] Figure 5 The γ′ phase morphology of GH4738 at different cooling rates, a is at a cooling rate of 20℃ / min, b is at a cooling rate of 100℃ / min, and c is at a cooling rate of 200℃ / min;
[0023] Figure 6 The γ′ phase morphology under different cooling rates under the amplification conditions of GH4738, the cooling rate of a is 20℃ / min, the cooling rate of b is 50℃ / min, the cooling rate of c is 100℃ / min, the cooling rate of d is 150℃ / min, and the cooling rate of e is 200℃ / min;
[0024] Figure 7 This is the corresponding relationship between the size of the γ′ phase and the cooling rate of the GH4738 alloy;
[0025] Figure 8 The corresponding relationship between the yield strength and cooling rate of GH4738 alloy;
[0026] Fig. 9 The corresponding relationship between the hardness and cooling rate of GH4738 alloy;
[0027] Fig.10 The morphology of γˊ phase precipitation after FGH95 alloy solid solution cooling at different cooling rates, the cooling rate of a is 20℃ / min, the cooling rate of b is 50℃ / min, the cooling rate of c is 100℃ / min, the cooling rate of d is 150℃ / min, and the cooling rate of e is 200℃ / min;
[0028] Fig.11 is the relationship between the size of γ′ phase and cooling rate of GH4151 alloy;
[0029] Fig.12 The corresponding relationship between the yield strength and cooling rate of FGH95 alloy;
[0030] Fig.13 This is the corresponding relationship between the hardness and cooling rate of FGH95 alloy. DETAILED DESCRIPTION
[0031] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0032] One aspect of the present invention relates to a method for analyzing the relationship between the solid solution continuous cooling rate and the microstructure and / or mechanical properties of a high-temperature alloy, comprising the following steps:
[0033] (a) The surface of the high-temperature alloy sample was coated with insulation materials of different thicknesses and then subjected to solution heat treatment, cooling and aging heat treatment;
[0034] (b) performing microstructural observation and / or mechanical property testing on the sample after the aging heat treatment to establish a correlation between the cooling rate and the microstructure and / or mechanical property.
[0035] The method for analyzing the relationship between the solid solution continuous cooling rate and the microstructure and / or mechanical properties of a high-temperature alloy is described. The surface of the high-temperature alloy sample is coated with insulation materials of different thicknesses, thereby changing the heat exchange boundary conditions, and can accurately control the cooling rate to achieve a cooling curve that is fast first and then slow, which is close to the actual working condition. The post-solid solution cooling rate corresponding to different areas of the disk / ring can be close to the cooling rate; the alloy micromorphology, structure and mechanical properties corresponding to different cooling rates are collected, and the correlation between the cooling rate and the structure morphology and / or mechanical properties is established, thereby determining the process control window for heat treatment of the high-temperature alloy.
[0036] Further, the cooling rate is 10-230°C / min, including but not limited to any point value of 10°C / min, 20°C / min, 50°C / min, 80°C / min, 100°C / min, 130°C / min, 150°C / min, 180°C / min, 200°C / min or 230°C / min or a range value between any two. Different parts of high-temperature alloy bars, disks, and rings have different cooling rates during the continuous cooling process, usually in the range of 10-230°C / min. The cooling rate is determined according to the actual cooling rate of the high-temperature alloy, and the correlation between the cooling rate and the microstructure and / or mechanical properties can be accurately analyzed.
[0037] The present invention precisely controls the cooling speed by coating the surface of the high-temperature alloy sample with insulation materials of different thicknesses. Due to the different thicknesses of the insulation materials, the cooling speed is also different. The specific correspondence between the thickness of the insulation material and the cooling speed is as follows:
[0038] When the cooling rate is controlled to be 10-30°C / min (for example, it may be but not limited to any one of 10°C / min, 15°C / min, 20°C / min, 25°C / min or 30°C / min or a range between any two of them), the thickness of the coated thermal insulation material is 50-70mm, including but not limited to any one of 50mm, 55mm, 60mm, 65mm or 70mm or a range between any two of them:
[0039] When the cooling rate is controlled to be 30-70°C / min (for example, it may be but not limited to any point value of 30°C / min, 35°C / min, 40°C / min, 45°C / min, 50°C / min, 55°C / min, 60°C / min, 65°C / min or 70°C / min, or a range value between any two of them), the thickness of the coated thermal insulation material is 15-30 mm, including but not limited to any point value of 15 mm, 20 mm, 25 mm or 30 mm, or a range value between any two of them:
[0040] When the cooling rate is controlled to be 70-130°C / min (for example, it may be but not limited to any point value of 70°C / min, 75°C / min, 80°C / min, 85°C / min, 90°C / min, 95°C / min, 100°C / min, 105°C / min, 110°C / min, 120°C / min, 125°C / min or 130°C / min, or a range value between any two of them), the thickness of the coated thermal insulation material is 6-10mm, including but not limited to any point value of 6mm, 7mm, 8mm, 9mm or 10mm, or a range value between any two of them;
[0041] When the cooling rate is controlled to be 130-170°C / min (for example, it may be but not limited to any point value of 130°C / min, 135°C / min, 140°C / min, 145°C / min, 150°C / min, 155°C / min, 160°C / min, 165°C / min or 170°C / min, or a range value between any two of them), the thickness of the coated thermal insulation material is 3-5mm, including but not limited to any point value of 3mm, 4mm or 5mm, or a range value between any two of them;
[0042] When the cooling rate is controlled to be 170-230°C / min (for example, it can be but not limited to any point value of 170°C / min, 180°C / min, 190°C / min, 200°C / min, 210°C / min, 220°C / min or 230°C / min, or a range value between any two of them), the thickness of the coated thermal insulation material is 0.5-2mm, including but not limited to any point value of 0.5mm, 1mm, 1.5mm or 2mm, or a range value between any two of them.
[0043] The cooling rate mentioned in the present invention is based on the center position of the test rod. Due to the small size of the test rod, the fluctuation of the cooling rate is generally between 1 and 3°C / min. The floating value of this cooling rate can be considered to have no effect on the tissue state at different positions of the test rod.
[0044] Furthermore, the thermal insulation material includes but is not limited to: at least one of fire-resistant thermal insulation wool, quartz tube or fiber felt.
[0045] Furthermore, an axial flow fan can be used to accelerate the cooling speed of the sample, and the wind speed is generally 5 to 60 m / s, including but not limited to any point value of 5 m / s, 10 m / s, 15 m / s, 20 m / s, 25 m / s, 30 m / s, 35 m / s, 40 m / s, 45 m / s, 50 m / s, 55 m / s or 60 m / s or a range value between any two of them.
[0046] Furthermore, the cooling method includes: air cooling and / or wind cooling.
[0047] Furthermore, the wind speed of the air cooling is 5 to 60 m / s, including but not limited to any point value of 5 m / s, 10 m / s, 15 m / s, 20 m / s, 25 m / s, 30 m / s, 35 m / s, 40 m / s, 45 m / s, 50 m / s, 55 m / s or 60 m / s or the range value between any two of them.
[0048] The solution heat treatment mentioned in the present invention refers to a heat treatment process in which the alloy is heated to a high temperature single-phase region and maintained at a constant temperature to allow the excess phase to fully dissolve into the solid solution, and then rapidly cooled to obtain a supersaturated solid solution.
[0049] Further, the temperature of the solution heat treatment is 960-1180°C, including but not limited to any point value of 960°C, 980°C, 1000°C, 1020°C, 1040°C, 1060°C, 1080°C, 1100°C, 1120°C, 1140°C, 1160°C or 1180°C or the range value between any two of them.
[0050] Furthermore, the holding time of the solution heat treatment is 1 to 6 hours, including but not limited to any one of 1h, 2h, 3h, 4h, 5h or 6h or a range between any two of them.
[0051] The aging heat treatment mentioned in the present invention refers to a heat treatment process in which a metal or alloy workpiece is subjected to solid solution treatment, high temperature quenching or a certain degree of cold working deformation, and then placed at a higher temperature or room temperature so that its performance, shape and size change over time.
[0052] Furthermore, the temperature of the aging heat treatment is 700-870°C, including but not limited to any point value of 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C or 870°C or a range value between any two of them.
[0053] Furthermore, the holding time of the aging heat treatment is 1 to 16 hours, including but not limited to any one of 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h or 16h or a range between any two of them.
[0054] Furthermore, the high temperature alloy sample includes but is not limited to: at least one of GH4169 alloy, GH4251 alloy, GH4738 alloy, GH4720Li alloy, FGH95 alloy or FGH96 alloy.
[0055] The present invention does not specifically limit the size of the high-temperature alloy sample, and can be designed according to the standard sample of the mechanical properties to be tested. In some specific embodiments, the high-temperature alloy sample includes but is not limited to: a cylindrical shape; the size of the high-temperature alloy sample is
[0056] In some specific embodiments, the heat insulating material is coated on the side wall of a cylindrical high-temperature alloy sample, and cotton caps are provided on both end surfaces, such as Figure 4 shown.
[0057] Another aspect of the present invention also relates to a method for optimizing the heat treatment process of a high-temperature alloy, including the method for analyzing the relationship between the solid solution continuous cooling rate and the microstructure and mechanical properties of the high-temperature alloy.
[0058] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0059] Example 1
[0060] GH4738 is a Ni-Cr-Co based precipitation hardening deformation high temperature alloy with an operating temperature below 815°C. Its chemical composition is shown in Table 1.
[0061] Table 1 GH4738 chemical composition (wt%)
[0062] Alloy / Element Cr Ti Al Co Ni Mass fraction (%) 18~15 2.75~3.25 1.2~1.6 12~15 Balanced
[0063] The solid solution continuous cooling test method was used to The GH4738 alloy test bars were tested, including the following steps:
[0064] 1. The surface of the GH4738 alloy test bar is coated with refractory insulation cotton of different thicknesses, and the test bar is cooled at cooling rates of 20℃ / min, 50℃ / min, 100℃ / min, 150℃ / min and 200℃ / min during the cooling process; when the cooling rate is controlled at 20℃ / min, the thickness of the coated refractory insulation cotton is 60mm; when the cooling rate is controlled at 50℃ / min, the thickness of the coated refractory insulation cotton is 23mm; when the cooling rate is controlled at 100℃ / min, the thickness of the coated refractory insulation cotton is 8mm; when the cooling rate is controlled at 150℃ / min, the thickness of the coated refractory insulation cotton is 4mm; when the cooling rate is controlled at 200℃ / min, the thickness of the coated refractory insulation cotton is 1mm;
[0065] 2. The GH4738 alloy test bar with the surface covered with refractory insulation cotton is subjected to solution heat treatment, and then air-cooled and aging heat treatment is performed after being taken out of the furnace; the solution heat treatment temperature is 1020°C, and the holding time is 2h; the aging heat treatment temperature is 800°C, and the holding time of the aging heat treatment is 8h;
[0066] 3. Conduct microstructural observation and mechanical property testing on samples after aging heat treatment to establish the correlation between cooling rate and microstructure morphology and mechanical properties.
[0067] Figure 5 The morphology of the precipitation phase of GH4738 at different cooling rates is shown in Figure 2. Figure 5 There are two sizes of γ′ phases: the large-sized initial γ′ phase with irregular shape near the grain boundary and the medium-sized spherical secondary γ′ phase. When the cooling rate increases from 20℃ / min to 200℃ / min, the initial γ′ phase and the secondary γ′ phase have no obvious changes in shape, but their sizes decrease.
[0068] Figure 6 To increase the magnification, the morphology of the γ′ phase precipitation of the GH4738 alloy is shown. As the cooling rate increases, the shape of the γ′ phase inside the test bar sample gradually changes from a rounded square to a round shape, and the size decreases at the same time.
[0069] Figure 7 The corresponding relationship between the size of the γ′ phase and the cooling rate of the samples with different cooling rates of GH4738 alloy was calculated using software. As the cooling rate increases from 20℃ / min to 50℃ / min, the average size of the γ′ phase decreases sharply from 0.26μm to 0.15μm, with a decrease of 3.6×10 -3 When the cooling rate increases from 50℃ / min to 100℃ / min, 150℃ / min and 200℃ / min, the average size of the γ′ phase gradually decreases from 0.11μm, 0.09μm, and finally to 0.055μm, with a reduction of only 0.8×10 -3 μm / (℃ / min), 0.4×10 -3 μm / (℃ / min) and 0.7×10 -3 μm / (℃ / min), the decrease is weakened. In the lower cooling rate stage, such as the cooling rate range of 20~50℃ / min, the precipitation size of γ′ phase of GH4738 alloy is most affected by the cooling rate.
[0070] Figure 8 The corresponding relationship between the yield strength and cooling rate of GH4738 alloy at different cooling rates is shown in Figure 2. Fig. 9The corresponding relationship between hardness and cooling rate. As the cooling rate increases, the yield strength of GH4738 alloy gradually increases. After reaching a cooling rate of 100℃ / min, the changes in yield strength and hardness values tend to be stable, and the effect of continuing to increase the cooling rate on both gradually weakens.
[0071] Example 2
[0072] FGH95 powder high temperature alloy is a high temperature and high strength nickel-based high temperature alloy. Its chemical composition is shown in Table 2.
[0073] Table 2 Chemical composition of FGH95 (wt%)
[0074] Alloy / Element Cr Ti Al Nb Co Ni Mass fraction (%) 9.0~13.0 2.6~3.0 3.5~4.0 3.2~3.6 13~17 Balanced
[0075] The solid solution continuous cooling test method was used to The FGH95 alloy test bar is tested, including the following steps:
[0076] 1. Same as Example 1;
[0077] 2. The FGH95 alloy test bar with the surface covered with refractory insulation cotton is subjected to solution heat treatment, and then air-cooled and aging heat treatment is performed after being taken out of the furnace; the solution heat treatment temperature is 1130°C, and the holding time is 2h; the aging heat treatment temperature is 850°C, and the holding time of the aging heat treatment is 10h;
[0078] 3. Same as Example 1.
[0079] Fig.10 This is the precipitation phase morphology of FGH95 alloy at different cooling rates. There are two sizes of large-sized γ′ phase in the figure. As the cooling rate increases, the shape of the γ′ phase inside the test bar sample gradually changes from an irregular square to a rounded square, and the size decreases at the same time.
[0080] Fig.11 The corresponding relationship between the size of the γ′ phase and the cooling rate of the FGH95 alloy samples with different cooling rates is statistically analyzed using software. As the cooling rate increases from 20℃ / min to 50℃ / min, the average size of the γ′ phase decreases sharply from 0.26μm to 0.15μm, with a decrease of 3.6×10 -3 When the cooling rate increases from 50℃ / min to 100℃ / min, 150℃ / min and 200℃ / min, the average size of the γ′ phase gradually decreases from 0.13μm, 0.12μm and tends to be stable, with a decrease of only 0.4×10 -3 μm / (℃ / min) and 0.2×10 -3μm / (℃ / min), the decrease is weakened. In the lower cooling rate stage, such as the cooling rate range of 20-50℃ / min, the precipitation size of the γ′ phase of FGH95 alloy is most affected by the cooling rate.
[0081] Fig.12 The corresponding relationship between the yield strength and cooling rate of FGH95 alloy at different cooling rates is shown in Figure 2. Fig.13 The corresponding relationship between hardness and cooling rate. As the cooling rate increases from 20℃ / min to 50℃ / min, the yield strength and hardness of FGH95 alloy increase simultaneously, but when the cooling rate increases to 100℃ / min, the yield strength and hardness values decrease simultaneously. When the cooling rate continues to increase to 150℃ / min, the influence of cooling rate on yield strength and hardness values gradually weakens, and both tend to be stable after increasing to the threshold.
[0082] Example 3
[0083] The solid solution continuous cooling test method was used to The GH4738 alloy test bars were tested, including the following steps:
[0084] 1. Quartz tubes of different thicknesses are coated on the surface of the GH4738 alloy test bar, and the test bar is cooled at cooling rates of 10°C / min, 30°C / min, 70°C / min, 130°C / min and 170°C / min during the cooling process; when the cooling rate is controlled at 10°C / min, the thickness of the coated quartz tube is 50mm; when the cooling rate is controlled at 30°C / min, the thickness of the coated quartz tube is 15mm; when the cooling rate is controlled at 70°C / min, the thickness of the coated quartz tube is 6mm; when the cooling rate is controlled at 130°C / min, the thickness of the coated quartz tube is 3mm; when the cooling rate is controlled at 170°C / min, the thickness of the coated quartz tube is 0.5mm;
[0085] 2. The GH4738 alloy test bar with the surface covered with refractory insulation cotton is subjected to solution heat treatment, and then air-cooled and aging heat treatment is performed after being taken out of the furnace; the solution heat treatment temperature is 1180°C, and the holding time is 1h; the aging heat treatment temperature is 700°C, and the holding time of the aging heat treatment is 16h;
[0086] 3. Conduct microstructural observation and mechanical property testing on samples after aging heat treatment to establish the correlation between cooling rate and microstructure morphology and mechanical properties.
[0087] Example 4
[0088] The solid solution continuous cooling test method was used to The FGH95 alloy test bar is tested, including the following steps:
[0089] 1. Fiber felts of different thicknesses were coated on the surface of the FGH95 alloy test bar, and the test bar was cooled at cooling rates of 30°C / min, 70°C / min, 130°C / min, 170°C / min and 230°C / min during the cooling process; when the cooling rate was controlled at 30°C / min, the thickness of the coated fiber felt was 70mm; when the cooling rate was controlled at 70°C / min, the thickness of the coated fiber felt was 30mm; when the cooling rate was controlled at 130°C / min, the thickness of the coated fiber felt was 10mm; when the cooling rate was controlled at 170°C / min, the thickness of the coated fiber felt was 5mm; when the cooling rate was controlled at 230°C / min, the thickness of the coated fiber felt was 2mm;
[0090] 2. The FGH95 alloy test bar with the surface covered with refractory insulation cotton is subjected to solution heat treatment, and then air-cooled and aging heat treatment is carried out after being taken out of the furnace; the solution heat treatment temperature is 960°C, and the holding time is 16h; the aging heat treatment temperature is 870°C, and the holding time of the aging heat treatment is 1h; the wind speed of air cooling is 30m / s;
[0091] 3. Conduct microstructural observation and mechanical property testing on samples after aging heat treatment to establish the correlation between cooling rate and microstructure morphology and mechanical properties.
[0092] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for analyzing the relationship between the solid solution continuous cooling rate and the microstructure and / or mechanical properties of a high-temperature alloy, characterized in that: The following steps are involved: (a) The surface of the high-temperature alloy sample was coated with insulation materials of different thicknesses and then subjected to solution heat treatment, cooling and aging heat treatment; (b) performing microstructural observation and / or mechanical property testing on the sample after the aging heat treatment to establish a correlation between the cooling rate and the microstructure and / or mechanical property.
2. The method for analyzing the relationship between the solid solution continuous cooling rate and the microstructure and / or mechanical properties of a high-temperature alloy according to claim 1, characterized in that: The cooling speed is 10-230°C / min.
3. The method for analyzing the relationship between solid solution continuous cooling rate and microstructure and / or mechanical properties of high-temperature alloy according to claim 1, characterized in that: When the cooling speed is controlled to be 10-30℃ / min, the thickness of the coated insulation material is 50-70mm: When the cooling speed is controlled to be 30-70℃ / min, the thickness of the coated insulation material is 15-30mm: When the cooling speed is controlled to be 70-130℃ / min, the thickness of the coated thermal insulation material is 6-10mm; When the cooling speed is controlled to be 130-170°C / min, the thickness of the coated thermal insulation material is 3-5mm; When the cooling speed is controlled to be 170-230°C / min, the thickness of the coated thermal insulation material is 0.5-2mm.
4. The method for analyzing the relationship between solid solution continuous cooling rate and microstructure and / or mechanical properties of high-temperature alloy according to claim 1, characterized in that: The heat insulating material comprises at least one of fire-resistant heat-insulating wool, quartz tube or fiber felt.
5. The method for analyzing the relationship between solid solution continuous cooling rate and microstructure and / or mechanical properties of high-temperature alloy according to claim 1, characterized in that: The cooling method includes: air cooling and / or wind cooling.
6. The method for analyzing the relationship between solid solution continuous cooling rate and microstructure and / or mechanical properties of high-temperature alloy according to claim 5, characterized in that: The wind speed of the air cooling is 5 to 60 m / s.
7. The method for analyzing the relationship between solid solution continuous cooling rate and microstructure and / or mechanical properties of high-temperature alloy according to claim 1, characterized in that: The temperature of the solution heat treatment is 960-1180°C; And / or, the holding time of the solution heat treatment is 1 to 6 hours.
8. The method for analyzing the relationship between solid solution continuous cooling rate and microstructure and / or mechanical properties of high temperature alloy according to claim 1, characterized in that: The temperature of the aging heat treatment is 700-870°C; And / or, the holding time of the aging heat treatment is 1 to 16 hours.
9. The method for analyzing the relationship between solid solution continuous cooling rate and microstructure and / or mechanical properties of high-temperature alloy according to claim 1, characterized in that: The high temperature alloy sample comprises at least one of GH4169 alloy, GH4251 alloy, GH4738 alloy, GH4720Li alloy, FGH95 alloy or FGH96 alloy.
10. A method for optimizing a high temperature alloy heat treatment process, characterized in that: The invention comprises the method for analyzing the relationship between the solid solution continuous cooling rate and the microstructure and / or mechanical properties of a high-temperature alloy as described in any one of claims 1 to 9.